Determinasi Perawi Hadis Kritik Atas Penilaianmuhammad Mustafa Al-Azami, Muh. Zuhri dan Marzuki Tentang Ibn Abi Laila Sebagai Rijal Al-Bukhari - M. Syukrillah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Bima, 2023)
The authenticity of the hadith sanad was evaluated by the quality of the transmitters or narrators. The identity of transmitters in an isnad was being evaluated as the first step. Particularly, determining the similar transmitter names and profiles (ta’yin wa tamyiz). The crucial step is to distinguish between the similar transmitters, then judge their reliability through the state of affairs transmitter in the ta'dil and jarh books. In this paper, I intend to examine the opinions of Muhammad Mustafa al-Azami, Muh Zuhri, and Marzuki on Ibn Abi Laila. They claim the weeknees of al-Bukhari’s hadis validity because of him in the isnad. Through library research, I argue that their opinion is false. Ibn Abi Laila is not a transmitter of Sahih Bukhari’s isnad. The misidentification of the transmitter was proven. In addition, this work proposes a method to limit misidentification in assessing and determining the transmitter.